Gouty Tophi: Two Case Report - Rosa Giménez-García; Gonzalo Cabezón-Villalba; Laura Perez-Gimenez; María Jesús Gimenez-Mazuelas (Dermatology, 2017)
Gouty tophi represent a symptom of chronic form of gout resulting from accumulation of monosodium urate crystals in tissues, which is the most prevalent form of inflammatory arthritis. The tophus represents a granulomatous inflammatory response to monosodium urate crystals. 1,2 Women are less likely to have gout than men but they develop it in the postmenopausal years and have comorbidities such renal disease, diabetes or concomitant use of diuretics more common as compared with men.3 We present two cases of gouty tophi.